A network analysis of DSM-5 posttraumatic stress disorder and functional impairment in UK treatment-seeking veterans. (June 2018) - Ross, Jana; Murphy, Dominic; Armour, Cherie
Highlights: PTSD symptoms B1, B2, D4, D6 and E4 were the most central symptoms. Functional impairment was related to a variety of PTSD symptoms. Impaired relationships were associated primarily with numbing symptoms. Impaired home management was associated primarily with reexperiencing symptoms. Abstract: Network analysis is a relatively new methodology for studying psychological disorders. It focuses on the associations between individual symptoms which are hypothesized to mutually interact with each other. The current study represents the first network analysis conducted with treatment-seeking military veterans in UK. The study aimed to examine the network structure of posttraumatic stress disorder (PTSD) symptoms and four domains of functional impairment by identifying the most central (i.e., important) symptoms of PTSD and by identifying those symptoms of PTSD that are related to functional impairment. Participants were 331 military veterans with probable PTSD. In the first step, a network of PTSD symptoms based on the PTSD Checklist for DSM-5 was estimated. In the second step, functional impairment items were added to the network. The most central symptoms of PTSD were recurrent thoughts, nightmares, negative emotional state, detachment and exaggerated startle response. Functional impairment was related to a number of different PTSD symptoms. Impairments in close relationships were associated primarily with the negative alterations in cognitions and mood symptoms and impairments in home management were associated primarily with the reexperiencing symptoms. The results are discussed in relation to previous PTSD network studies and include implications for clinical practice.